Awareness of Chicken Slaughterhouse Business Actors Towards Halal Products - Nafisah, Basmah; Fajriati, Imelda (Halal Research, 2024)
This study aims to provide an empirical picture of halal awareness of chicken slaughterhouse business actors towards halal certification in Indonesia by understanding halal perceptions and the extent of halal risks, critical points, and critical processes in their chicken slaughterhouses. This study uses a descriptive qualitative approach with field research methods. The research informants were two chicken slaughterhouse business actors: Mr. Wafir from RPA Semerak and Mr. Isa from RPA Master Chick. Data were obtained through interviews and documentation, with qualitative analysis using deductive methods. Planning Behavior Theory (SDG) is used to understand business actors' perceptions of halal certification, focusing on actual behavior, intentions, attitudes, and knowledge. The results showed that RPA Semerak already has awareness of halal production but does not have awareness of the obligation of halal certification, which is caused by the lack of public and business actors' understanding of the critical point and urgency of halal certification. In addition, tipping point activity related to chicken slicing after slaughter has not yet been considered. As for the RPA Master Chick, despite having awareness about halal certification, it still lacks a thorough understanding of knowledge. The results of this research are expected to contribute to increasing the understanding and awareness of chicken slaughterhouse business actors towards halal certification, as well as assisting related parties in designing education and training programs that are in accordance with the needs of the industry.